2010
DOI: 10.1523/jneurosci.1814-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

GABABReceptor Modulation of Serotonin Neurons in the Dorsal Raphé Nucleus and Escalation of Aggression in Mice

Abstract: The serotonin (5-HT) system in the brain has been studied more than any other neurotransmitter for its role in the neurobiological basis of aggression. However, which mechanisms modulate the 5-HT system to promote escalated aggression is not clear. We here explore the role of GABAergic modulation in the raphé nuclei, from which most 5-HT in the forebrain originates, on escalated aggression in male mice. Pharmacological activation of GABA B , but not GABA A , receptors in the dorsal raphé nucleus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 75 publications
8
96
0
2
Order By: Relevance
“…Serotonin (5-HT) is one of the major neurotransmitters that has crucial role on sleep-wake cycle, motor control, immune system, nociception, behavior and aggression regulation in species ranging from invertebrates to humans. In the CNS, 5-HT derives mainly from the midbrain raphe´ nuclei [20,21] . Since years ago, it has been known that serotonin acts in mood regulation [22] but recently it is identified that the 5-HT has important role in the central control of feeding behavior in mammals and avian species.…”
Section: Serotoninmentioning
confidence: 99%
“…Serotonin (5-HT) is one of the major neurotransmitters that has crucial role on sleep-wake cycle, motor control, immune system, nociception, behavior and aggression regulation in species ranging from invertebrates to humans. In the CNS, 5-HT derives mainly from the midbrain raphe´ nuclei [20,21] . Since years ago, it has been known that serotonin acts in mood regulation [22] but recently it is identified that the 5-HT has important role in the central control of feeding behavior in mammals and avian species.…”
Section: Serotoninmentioning
confidence: 99%
“…We used an autoreceptor agonist, 8-OH-DPAT, as a pharmacological tool to transiently inhibit 5-HT impulse flow from the DRN (Sprouse and Aghajanian, 1987;Will et al, 2004) during testing for aggressive behavior. As intra-DRN infusion of 8-OH-DPAT has been reported to reduce aggressive and motor behaviors in mice in higher doses (1 mg; Faccidomo et al, 2008), we selected a lower dose, 0.3 mg, so that baseline aggression and motor activity would be preserved, as shown by Takahashi et al (2010b). After drinking water or 1.0 g/kg of alcohol, mice received intra-DRN microinfusions of 0.3 mg CP-154,526 alone, 0.3 mg 8-OH-DPAT alone, a combination of CP-154,526 and 8-OH-DPAT, or vehicle in counterbalanced order and subsequently tests for aggressive behavior commenced.…”
Section: Intra-drn Microinjection Of Crf-r1 Antagonists and 8-oh-dpatmentioning
confidence: 99%
“…This means that the amplification effect of GABA B agonist baclofen on aggression is dependent on the activation of serotonin neurons. It should be mentioned that both GABA A and GABA B receptors are expressed in the dorsal raphe nucleus of mice and play a role in the aggression behavior (Takahashi et al, 2010a;2010b). On the other hand, according to the report of Cherek et al (2002), amygdala is one of the brain structures involved in aggression, possibly due to several neurotransmitters such as GABA and serotonin (Cherek et al, 2002).…”
Section: Discussionmentioning
confidence: 99%